2005
DOI: 10.1016/s0002-9440(10)61184-4
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Tumor Vessel Supply in Lewis Lung Carcinoma in Mice by Fluorescent Microsphere Distribution and Imaging with Micro- and Flat-Panel Computed Tomography

Abstract: In lung carcinomas the blood supply varies depending on tumor type and stage and can develop from pulmonary or bronchial circulation, or both. To examine this in vivo, primary bronchogenic Lewis lung carcinoma cells were intratracheally instilled in C57BL/6 mice. Within 7 days, histological examinations showed progressive tumor growth at the peripheral parenchymal region. The relative contribution of tumor blood supply via the pulmonary and systemic arteries was studied in detail using fluorescent microspheres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
28
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 25 publications
3
28
0
Order By: Relevance
“…In this regard, an earlier study of our group has shown that the pulmonary artery plays a major role in delivering blood supply to LLC1 lung tumors. 2 This finding is in accordance with the observation that jugular vein catheter injection of PEI-complexed siRNA is particularly appropriate for targeting of lung tumor tissue through the pulmonary artery. The finding that LLC1 lung cancer tissue was transfected by siRNA with a higher efficiency than healthy lung tissue is most likely because of anatomical and functional changes to the tumor vessels.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…In this regard, an earlier study of our group has shown that the pulmonary artery plays a major role in delivering blood supply to LLC1 lung tumors. 2 This finding is in accordance with the observation that jugular vein catheter injection of PEI-complexed siRNA is particularly appropriate for targeting of lung tumor tissue through the pulmonary artery. The finding that LLC1 lung cancer tissue was transfected by siRNA with a higher efficiency than healthy lung tissue is most likely because of anatomical and functional changes to the tumor vessels.…”
Section: Discussionsupporting
confidence: 89%
“…2 In this model, we demonstrated that tumor vascularization arises primarily from the pulmonary artery. This model has now been employed to compare different routes of in vivo siRNA administration for targeting lung tumors.…”
Section: Introductionmentioning
confidence: 80%
See 1 more Smart Citation
“…The total length of the canula from needle point to the end of canula was 28 mm. A longer canula can puncture the outer surface of the lung parenchyma, while a shorter canula will result in instillation in the higher regions of the lung, similar to what Savai et al 13 reported. High instillation of the tumour cells makes accurate discrimination of the tumour from other dense tissues such as the heart with CT more complicated.…”
Section: Preparation Of the Canulasupporting
confidence: 76%
“…Lewis lung carcinoma (LLC) was isolated from the epidermoid carcinoma of the lung in mice. It is regarded as an essential tumor model in studies of metastasis (4,5), vessel formation (6), and effects of therapy (7). A tumor-bearing model of mice with LLC exhibits a greater metastatic potential than a tumor-bearing model alone (8,9).…”
Section: Introductionmentioning
confidence: 99%